2014
DOI: 10.1111/and.12256
|View full text |Cite
|
Sign up to set email alerts
|

Impact of varicocelectomy on premature ejaculation in varicocele patients

Abstract: In a prospective manner, we studied the effect of varicocelectomy on premature ejaculation and testicular hormonal function in patients with varicocele. Microsurgical subinguinal varicocelectomy was carried out in 73 patients with clinical varicocele associated with premature ejaculation (group 1) and compared with 56 patients without operative intervention (group 2; control). The primary efficacy variable was the mean change in the Premature Ejaculation Diagnostic Tool. The changes in International Index of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The authors also note that venous congestion through a connection between the testicular and prostatic venous systems may predispose a varicocele patient to prostatitis. Consistent with these findings, there have been preliminary reports from methodologically flawed studies of improvements in men with PE treated with varicoelectomy (138,139). …”
Section: Varicocele and Pementioning
confidence: 53%
“…The authors also note that venous congestion through a connection between the testicular and prostatic venous systems may predispose a varicocele patient to prostatitis. Consistent with these findings, there have been preliminary reports from methodologically flawed studies of improvements in men with PE treated with varicoelectomy (138,139). …”
Section: Varicocele and Pementioning
confidence: 53%
“…Even when viewed from this lens, one cannot ignore the number of well-fashioned studies that include relatively large numbers of subjects. 24,26,[28][29][30][31] Although a great deal of work has thus established the link between varicocele and decreased androgen production, the pathophysiologic principles that result in this association have yet to be identified.…”
Section: Contemporary Evidencementioning
confidence: 99%
“…These results mirror prior literature demonstrating improved SA results in men with abnormal SA and varicocele, which suggests that varicocele, Sertoli cell and Leydig cell dysfunction may be intertwined. In addition to the above data, Ahmed et al demonstrated improvement in TT in 81.8% of men with low TT compared to only 17.5% with normal TT (42). Interestingly, Zhody et al (38) and Srini et al (39) also noted that men who did not undergo repair had decreased TT.…”
Section: Varicocelectomy In Hypogonadal Menmentioning
confidence: 82%
“…This was most prominently observed in hypogonadal men or men with low-normal TT. Of the fifteen studies with increased TT, twelve (22,26,27,30,38-43,49,50) were with average initial TT <400 ng/dL with six of seven prospective studies in hypogonadal or low-normal TT levels (27,38,39,41,42,49). When weighted according to patient population, the average starting TT for those with increased TT was 326 ng/dL while the average TT for those without increased TT was 535 ng/dL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation